Barriers to brain health behaviours: results from the Five Lives Brain Health Ireland Survey - Dukelow, Tim; Vassilev, Philip; Lawrence, Erin Grace; Jacobson, Liron; Koychev, Ivan; Muhammed, Kinan; Kennelly, Sean P. (Frontiers in Psychology, 2023)
Modifiable risk factors for dementia remain prevalent in Ireland. A detailed examination of barriers to risk reduction behaviours in an Irish context has heretofore been lacking. Many existing studies examining barriers to brain health behaviours fail to examine how they might vary across different modifiable risk factors. This study undertook a detailed assessment of barriers to individual risk reduction behaviours. As existing research suggests that barriers may vary across sociodemographic factors, we sought to investigate the distribution of barriers across age, gender, educational status, and household income. The Five Lives Brain Health Ireland Survey is a cross-sectional survey that was distributed online amongst a non-patient population. The survey captured the following: (1) Sociodemographic factors; (2) Barriers to brain health behaviours; (3) Exposure to, and knowledge of, modifiable risk factors for dementia, namely diet, social interaction, exercise, hypertension, sleep, current low mood/depression, current smoking, alcohol consumption, cognitive stimulation, hearing impairment, diabetes, air pollution, and head injury; (4) Participants’ perceptions regarding potential for dementia prevention, and risk reduction. Lack of motivation was the most prevalent barrier to consuming a healthy diet (64%, n = 213), physical activity (77.7%, n = 167), smoking cessation (68%, n = 85), and moderation of alcohol intake (56.3%, n = 67). Practical factors were the most prevalent barriers to addressing low mood (56.5%, n = 87), air pollution (30.1%, n = 58), hearing impairment (63.8%, n = 44), diabetes (11.1%, n = 5), and head injury (80%, n = 8). Emotional factors were the most prevalent barriers to engaging in mentally stimulating activity (56.9%, n = 66), social activity (54.9%, n = 302), and good sleep (70.1%, n = 129). Lack of knowledge was the most prevalent barrier to hypertension control (14.4%, n = 29). Distribution of barriers varied across age, gender, educational status, and household income. This study investigated barriers to lifestyle change to improve brain health in an Irish sample of adults aged 50 and above. Detailed subtyping of barriers, as well as examination of differences according to age, gender, education, and income were undertaken. The heterogeneity of barriers to brain health behaviours revealed in this study highlights the necessity to tailor public health interventions to their target population, taking into account the gender, age, educational status, and income of recipients.